Disorders in the temporomandibular joints in pediatric patients - frequency of physiotherapy visits - Kasperkowicz, Joanna; Malak, Roksana; Matthews-Brzozowska, Teresa; Samborski, Włodzimierz; Mojs, Ewa (Journal of Education, Health and Sport, 2022)
Introduction: Temporomandibular disorders can be a challenge for both clinicians and patients. It is unclear what factors are associated with prolonged conservative care and patient dissatisfaction with treatment outcomes. Material and research method: A literature review was carried out in terms of methods of physiotherapeutic treatment following disorders of temporomandibular joints in pediatric patients. This work is for reference only. The PubMed and Google Schoolar databases were analyzed. The keywords used in the search were: "physiotherapy, temporomandibular joints and children", "manual therapy, temporomandibular joints and children". The authors focused on reports published in Polish and English from the last 10 years. Results: There is a need to combine standard therapy with physiotherapy in order to accelerate the treatment process. Conclusions: Physiotherapy is highly effective and non-invasive in the treatment of stomatognathic system disorders. A physiotherapist provides a number of therapeutic treatments that improve disorders in the temporomandibular joints.